2016
DOI: 10.1111/jcms.12383
|View full text |Cite
|
Sign up to set email alerts
|

China, the European Union and the Fragile World Order

Abstract: The EU (European Union) and China are the two arguably most unusual powers in today's world: the EU as the most integrated regional association of states and China as the largest developing great power. As the post-Cold War American-led liberal world order is facing challenges from forces unleashed by the power transition and power diffusion in the international system, this article will look into the order-shaping roles of the EU and China, to identify their respective visions of a desirable world order and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The fact that key institutions of global economic and financial governance have been dominated by the United States and the EU, with an informal arrangement that reserves the leadership of the World Bank Presidency for an American and of the International Monetary Fund (IMF) for the Europeans, has caused considerable rancor among emerging countries, including China. China, together with others, pushed for reform of the IMF in 2010, but when this "reordering from within" failed to deliver results, it switched to a different "reordering from outside" strategy (Chen 2015). This new strategy of setting up alternative multilateral institutions outside the liberal order includes the New Development Bank (set up together with fellow BRICS [Brazil, Russia, India, China, and South Africa] states) and the Asian Infrastructure Investment Bank (AIIB) (set up together with other Asian countries).…”
Section: China-eu Relations In the Context Of Multilateral Institutionsmentioning
confidence: 94%
“…The fact that key institutions of global economic and financial governance have been dominated by the United States and the EU, with an informal arrangement that reserves the leadership of the World Bank Presidency for an American and of the International Monetary Fund (IMF) for the Europeans, has caused considerable rancor among emerging countries, including China. China, together with others, pushed for reform of the IMF in 2010, but when this "reordering from within" failed to deliver results, it switched to a different "reordering from outside" strategy (Chen 2015). This new strategy of setting up alternative multilateral institutions outside the liberal order includes the New Development Bank (set up together with fellow BRICS [Brazil, Russia, India, China, and South Africa] states) and the Asian Infrastructure Investment Bank (AIIB) (set up together with other Asian countries).…”
Section: China-eu Relations In the Context Of Multilateral Institutionsmentioning
confidence: 94%
“…Although stressing the importance of the need to reform the institutions of the liberal international order to better reflect the interests of the developing countries, China, in the late twentieth century, became part of this order and acted as an 'order-taker' while at the same time keeping a low profile and concentrating its efforts on the continuation of Deng Xiaoping's policy of 'reform and opening' (Chen, 2016). Although this order was designed by and for Western powers, it did nevertheless give China the opportunity for global engagement (Men et al, 2020).…”
Section: The Rise Of China and The Liberal International Ordermentioning
confidence: 99%
“…The broad literature on global order has identified the deeper roots of divisions within the international community and the challenges to Western liberalism. One reason is the failure to reform the global institution of the ‘American‐led hierarchical liberal order’ (Chen, , pp. 776–777), which consequently led to creation of alternative regional institutions such as the Asian Infrastructure Investment Bank, the failed military interventions in Iraq or Afghanistan, and the extension of globalisation processes encompassing the fields of economics, finance, technology, communication and security.…”
Section: Trends Accelerating Western Declinementioning
confidence: 99%
“…In 2014, the annexation of Crimea by Russia led to questioning the resilience and persistence of the rules-based security order in Europe (for instance, Schwarzer and Stel-zenm€ uller, 2014;Chen, 2016). Mikhail Gorbachev (2015) has suggested that the world is entering 'a new Cold War order' while Kofi Annan (2015) has called for global leaders to save the global order, identifying the annexation of Crimea, the wars in Syria and Iraq, climate change and international trade as issues that could divide the international state community along new battle lines.…”
Section: Challenges To Western Liberalismmentioning
confidence: 99%
See 1 more Smart Citation